An analysis of the harassments and challenges faced by the public transport users in a developing country of South Asia - Yasir, Samnun; Ahmad, Tanzim; Enam, Annesha (Frontiers in Built Environment, 2022)
Bangladesh – located in south Asia and home to almost 167 M people, is one of the most densely populated countries in the world. Despite high population density, the country is yet to have a well-coordinated mass transit system. However, most people rely on public transportation due to comparatively low motorization. Public transport users, especially vulnerable cohorts (e.g., women), face enormous challenges, including molestations, assaults, and rape during their daily commute. Few studies that analyzed the state of harassment exclusively focused on women, which might not be comprehensive enough to understand the state of the problem and devise effective policies. Therefore, the current study explores the state of harassment in the three cities of Bangladesh, namely, Dhaka - the capital; Rajshahi; and Mymensingh across all genders. The study also investigates people’s perception of women's mobility, the experience of using public transport, and the desirable safety precautions to understand the gender differences and the variability across the three cities. A detailed questionnaire survey was conducted to collect data from the three cities. The study found considerable gender differences regarding the perception of women's mobility hindrances, the experience of using public transportation, and desirable safety precautions. The differences across the three cities were also noticeable. Contrary to the general belief, the study found that people from smaller towns like Mymensingh were more likely to get harassed than those from the bigger cities like Dhaka and Rajshahi – insinuating the lack of reporting from the smaller towns of the country. The findings from the study could be helpful for the transit and city planners in creating a conducive transit ambiance in Bangladesh. Based on the desirable safety precautions, female-only rides, especially at night, would be beneficial. City planners could also plan small and medium business activities around transit stops to attract the crowd and reduce the possibility of getting harassed while walking alone to access transit.